Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1073/pnas.0808671106
|View full text |Cite
|
Sign up to set email alerts
|

A microtubule depolymerizing kinesin functions during both flagellar disassembly and flagellar assembly in Chlamydomonas

Abstract: Cilia and flagella are dynamic organelles that are assembled and disassembled during cell differentiation, during stress, and during the cell cycle. Although intraflagellar transport (IFT) is well documented to be responsible for transport of ciliary/flagellar precursors from the cell body to the flagella, little is known about the molecular mechanisms for mobilizing the cell body-localized precursors to make them available for transport during organelle assembly or for disassembling the microtubule-based axon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
161
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 129 publications
(168 citation statements)
references
References 46 publications
5
161
0
Order By: Relevance
“…Studies in Ochromonas show that cytoplasmic microtubules may play a role in flagellar regeneration (Brown and Bouck, 1973). Previously, we have shown that kinesin-13 in Chlamydomonas (CrKin13) undergoes protein phosphorylation and is involved in proper flagellar assembly (Piao et al, 2009). In this report, we characterized dynamic changes of cytoplasmic microtubules during flagellar regeneration and found that cytoplasmic microtubules were quickly depolymerized to provide tubulin precursors for flagellar assembly, which required CrKin13.…”
Section: Introductionmentioning
confidence: 84%
“…Studies in Ochromonas show that cytoplasmic microtubules may play a role in flagellar regeneration (Brown and Bouck, 1973). Previously, we have shown that kinesin-13 in Chlamydomonas (CrKin13) undergoes protein phosphorylation and is involved in proper flagellar assembly (Piao et al, 2009). In this report, we characterized dynamic changes of cytoplasmic microtubules during flagellar regeneration and found that cytoplasmic microtubules were quickly depolymerized to provide tubulin precursors for flagellar assembly, which required CrKin13.…”
Section: Introductionmentioning
confidence: 84%
“…EB3 interacts with the MT depolymerizing kinesin-13 MCAK (Lee et al, 2008). Kinesin-13 family proteins have been implicated in cilium disassembly in protists (Blaineau et al, 2007;Dawson et al, 2007;Piao et al, 2009), and EB3 might, therefore, stabilize the axoneme by counteracting such proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Mice with mutations of the Kif19a gene showed elongated cilia in brain, oviduct and tracheal epithelial cells, suggesting an important role for this protein in ciliary length regulation (Niwa et al, 2012). Although the Chlamydomonas homolog of kinesin-13 family proteins, CrKinesin-13 was not seen at the flagellar tip, RNAimediated depletion of this protein resulted in cells with shorter flagella that failed to regenerate after deflagellation (Piao et al, 2009), suggesting a role for CrKinesin-13 in flagellar assembly. Similarly, depletion of Kif24, a kinesin-13 family protein that specifically depolymerizes centriolar MTs, resulted in aberrant cilia (Kobayashi et al, 2011).…”
Section: Introductionmentioning
confidence: 98%